Liver transplantation and adolescence: The role of mental health. Issue 11 (November 2016) - Hames, Anna; Matcham, Faith; Joshi, Deepak; Heneghan, Michael A.; Dhawan, Anil; Heaton, Nigel; Samyn, Marianne
Abstract : Young people (YP) with chronic illness have higher rates of mental health problems than the general population, with psychosocial complexity associated with nonadherence and poorer health outcomes. This study aimed to describe the prevalence of anxiety and depression in YP after liver transplantation, with autoimmune liver disease and other chronic liver diseases, identify the factors YP attribute their distress to and the relationship between anxiety/depression, and describe YP's beliefs about their illness and treatment. An electronically administered questionnaire battery was given routinely to YP attending an outpatient liver transition clinic; 187 YP participated, of which 17.7% screened positive for anxiety or depression. There were no significant differences between disease groups. This is significantly higher than the prevalence of common mental health problems in the general adolescent population. Patients most frequently attributed their distress to fatigue, sleep difficulties, financial concerns, problems at work/school, worry, and low self‐esteem. Higher levels of depression and anxiety were significantly associated with specific illness and treatment beliefs but not with perceived understanding of illness or treatment control. In conclusion, the increased prevalence of mental health problems in YP and the intertwined nature of these with their physical health outcomes provide evidence that holistic care should be delivered as standard for this age group. Liver Transplantation 22 1544–1553 2016 AASLD .